Ticraḍ, gar usemres d wazal n yizamulen i d-mmalent - Ourida AISSOU (Ussnan)
This contribution aims to describe the practice of tattooing in some Amazigh regions. It tries to list the different techniques, the actors plus the means used to succeed in this practice which has a high value in the society. The use of tattooing is multifunctional; it helps treat some illnesses such as goiter, migraine and rheumatism, as it plays a protective role against bad oil and sterility. The objective of this contribution is to highlight the value of tattooing in Amazigh society and attempt to reveal the secret of some tattoo symbols.